PENINGKATAN HASIL BELAJAR PENDIDIKAN PANCASILA MENGGUNAKAN MODEL GAME BASED LEARNING (GBL) BERBANTUAN BAAMBOOZLE DI KELAS V SDS IT LUQMAN KOTA PADANG - Fadhilah, Hasnatul; Waldi, Atri; Reinita; Tri Wulandari, Fikhen (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study is grounded in the low learning achievements of fifth-grade students at SDS IT Luqman in Padang City in the subject of Pancasila Education, as evidenced by their minimal learning interest, passive participation, and challenges in mastering core concepts—a situation that also impedes the development of critical thinking, problem-solving, and communication skills. The learning process has yet to fully embody the principles of deep learning, thereby positioning the implementation of a Game-Based Learning model assisted by the Baamboozle platform as a viable solution. The objective is to delineate the enhancement of Pancasila Education learning outcomes through this model. Employing a Classroom Action Research (CAR) design with a mixed qualitative-quantitative approach, the implementation comprised two cycles (Cycle I: two meetings; Cycle II: one meeting), adhering to the phases of planning, action, observation, and reflection. Instruments included RPPM observation sheets, teacher-student activity sheets, and rubrics for assessing attitudes, knowledge, and skills, with 21 fifth-grade students as subjects. Findings highlight substantial improvements: RPPM scores rose from 84.3% to 96.8%; teacher activity from 82.1% to 96.4%; student activity from 76.75% to 92.85%; and average learning outcomes advanced from 70.5 to 78.3, culminating at 91.83 by the end of the cycle.